COMPARISON OF DIFFERENT DOSES OF TRANEXAMIC ACID ON POST-OPERATIVE BLEEDING IN PATIENTS OF CABG SURGERY - Fayaz, Fakher -e-; Ahmed, Iftikhar; Khurshid, Hana (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare three different dosing schedules of tranexamic acid to achieve good hemostasis intraoperatively and in post-operative period.Design: Randomized controlled trials.Place and Duration of Study: Anaesthesia department, Armed Forces Institute of Cardiology/National Institute of Heart Diseases (June 2011 to Jan 2013)Patients and Methods: A total of 128 patients, due for coronary artery bypass grafting were included in this study after informed consent. The patients were randomly divided into four groups. Group A, being the control group, did not receive tranexamic acid during the operation, whereas the remaining three groups received tranexamic acid just after the reversal of heparin with protamine sulphate. Group B received low dose, group C received medium dose and group D received high dose of tranexamic acid both as bolus and followed by infusion. Six patients, 4 from group B and 2 from group D were dropped out due to incomplete data or some complication. The blood loss at 6 hours and 24 hours after surgery were noted along with amount and type of transfusions needed and clinical outcomes. The total cardio-pulmonary bypass time, aortic cross-clamp time and chest closure time were also noted. Haemoglobin levels, coagulation profile and activated clotting time were noted and compared pre and post operatively.Results: All the 4 groups were comparable with respect to age, weight, gender and personal history. Average bleeding in group A was similar to group B after six hours (p = 0.755) and 24 hours (p = 0.343) but significantly higher as compared to group C (p < 0.001) and group D (p < 0.001). Group B also had more blood in chest drain as compared to group C (p < 0.001) and group D (p < 0.001). Group C and group D had almost similar amount of blood loss after 6 hours (p = 0.916) as well as after 24 hours (p = 0.834).Conclusion: This study showed that tranexamic acid, when given at a loading dose of 20 mg/kg or greater and followed by a maintenance infusion of 15 mg/kg/hr or greater, significantly reduced the amount of blood loss, both intra-operatively and post- operatively, in patients undergoing on-pump coronary artery bypass grafting.